Induction of apple tree budding by hydrogenated cyanamide and mineral oil under influence of temperature - Petri, José Luiz (Pesquisa Agropecuaria Brasileira, 1997)
Dormancy breaking in apple (Malus domestica B.) orchards with chemicals is a very common practice in regions with mild winter. When mineral oil and dinitro-ortho-cresol (DNOC) are recommended, they are used at temperatures above 20°C. The effect of other temperatures on the efficiency of hydrogenated cyanamide and mineral oil is not known. In this work the effect of temperature on hidrogenated cyanamide and mineral oil on dormancy breaking of apple trees was evaluated. Apple scions of cultivars Gala and Fuji received a treatment with mineral oil at 4% plus hydrogenated cyanamide at 0.25% and were submitted to different combinations of temperature before and after having received the chemical treatment. The trial was carried out during three years. Percentage of bud breaking was evaluated at 40 and 60 days after treatments were performed. This breakage strongly increased when mineral oil treatment (4%) and hydrogen cyanamide (0.25%) were used. Temperatures of 4oC three days before or after application did not reduce the efficiency of mineral oil plus hydrogenated cyanamide. This aspect allows concluding that the efficiency of mineral oil plus hydrogenated cyanamide is not related to the temperature.